Surface agents' influence on the flexural strength of bilaminated ceramics - Lima, Júlia Magalhães Costa [UNESP]; Anami, Lilian Costa [UNESP]; Rippe, Marília Pivetta [UNESP]; de Melo, Renata Marques [UNESP]; Bottino, Marco Antonio [UNESP]; Valera, Márcia Carneiro [UNESP]; Araújo, Maria Amélia Máximo [UNESP] (FapUNIFESP (SciELO), 2013)
The objective of this study was to evaluate the influence of different surface agents on the flexural strength of a ceramic system. Eighty bar-shaped specimens of zirconia were divided into four groups according to the agent to be used: group Control-to be cleaned with alcohol; group VM9-application of a fluid layer of porcelain; group Effect Bonder-application of a bonding agent; and group Coloring Liquid-application of coloring liquid. All specimens received the porcelain application by the layering technique and were then subjected to thermocycling. The four-point bending test was performed to calculate the strength values (s, MPa) and the failure modes were classified. ANOVA did not detect significant differences among the groups. The Weibull modulus were 5 (Control, VM9 and Effect Bonder) and 6 (Coloring Liquid). The cracking of the porcelain ceramic toward the interface was the predominant failure mode. It was concluded that the surface agents tested had no effect on the flexural strength of the bilaminated ceramic specimens.
Keywords: Ceramics; Compressive strength; Dental materials; Fractures; Stress